2009
DOI: 10.1177/0969733009097992
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Advocacy in Procedural Pain Care

Abstract: In nursing, the concept of advocacy is often understood in terms of reactive or proactive action aimed at protecting patients' legal or moral rights. However, advocacy activities have not often been researched in the context of everyday clinical nursing practice, at least from patients' point of view. This study investigated the implementation of nursing advocacy in the context of procedural pain care from the perspectives of both patients and nurses. The cross-sectional study was conducted on a cluster sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 50 publications
(44 reference statements)
2
25
1
7
Order By: Relevance
“…Similarly, studies in different contexts and clinical situations have shown that patient advocacy can be considered a moral commitment of nurses, aimed especially at counseling patients about their rights and helping them in the decision-making process and ensuring the exercise of their autonomy (7)(8)(9)(10)14,17) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, studies in different contexts and clinical situations have shown that patient advocacy can be considered a moral commitment of nurses, aimed especially at counseling patients about their rights and helping them in the decision-making process and ensuring the exercise of their autonomy (7)(8)(9)(10)14,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence indicating the need to pursue it as a career goal in nursing, there still is not a defined concept for patient advocacy. In 1973, international nursing practice codes included patient advocacy as an ethical and legal role for nurses and since then several studies have pointed to actions and features that are intended to assist and expand the exercise of patient advocacy in nursing practice (7)(8)(9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advocacy seems to have a close relation with power, and it can be seen as a motivational construct for nursing, enabling the facing of the physical and social demands of the health environments (17) .…”
Section: Advocacy Of User: a Concept To Be Rescuedmentioning
confidence: 99%
“…It can no longer be neglected the fact that the classroom is still the most radical environment to start the process of resistance of the nursing professionals, so that they become more critical, reflective and, mainly, with actively reverberating voices in society (17) .…”
Section: Referrals and Possibilitiesmentioning
confidence: 99%